Language, Knowledge, and Representation
XII, 180 p. 4 illus.
Keywords: Every two years since 1989, an international colloquium on cognitive science is held in Donostia - San Sebastian, attracting the most important researchers in that field. This volume is a collection of the invited papers to the Sixth International Colloquium on Cognitive Science (ICCS-99), written from a multidisciplinary, cognitive perspective, and addressing various essential topics such as self-knowledge, intention, consciousness, language use, learning and discourse. This collection reflects not only the various interdisciplinary origins and standpoints of the participating researchers, but also the richness, fruitfulness, and exciting state of research in the field of cognitive science today. A must-read for anyone interested in philosophy, linguistics, psychology, and computer science, and in the perception of these topics from the perspective of cognitive science.